(untitled) (Research, Society and Development, 2020)
This work presents a theoretical study of the heat and mass transfer during the drying of industrial ceramic bricks in an oven. Mathematical models have been proposed to describe the drying and heating kinetics of the brick as a function of the process time, considering the existence of the internal and external surface areas and dimensional variations of the brick. Empirical models have been proposed to predict the behavior of moisture content, surface temperature, volume and internal and external surface areas of the product. The study was conducted under different operating conditions of the drying-air (50 to 100°C). The entire modeling was fitted to experimental data of the average moisture content, temperature on the surface and average dimensions of the brick during drying, in each experimental condition, obtaining a good fit and high coefficient of determination, showing its reliability to be used in the prediction of the physical problem. From the comparison, the volume, the internal and external surface areas and the heat and mass transfer parameters of the brick were estimated.